Cognitive product development - Gielingh, Wim (Strojniški vestnik, 2008)
In current engineering practice, designers usually start a new project with a blanc sheet of paper or an empty modeling space. As a single designer has not all knowledge about all aspects of the product, the design has to be verified by other experts. The design may have to be changed, is further detailed, again verified and approved, and so on, until it is ready. But only the final product, once it exists, will prove the correctness of the design. Given the complexity of modern industrial products, the intermediate verification and change processes require substantial time. This has a major negative impact onthe development time and costs of the product. Cognitive Product Development, as proposed here, approaches design as a scientific learning process. It is based on a well known and successfully applied theory for Cognitive Psychology. In stead of relying solely on the experiences of a single individual, CPD makes the combined knowledge of multiple disciplines, acquired throughout the life of existing products, available through generic design objects. CPD thus approaches design as the configuration of existing and verified knowledge. It is expected that this accelerates the product development process and results in designs of higher quality and reliability without affecting the creative freedom of the designer.
Keywords: razvoj izdelkov; konstruiranje; metode; modeliranje